STRATEGI KEUANGAN YANG DITERAPKAN DALAM SEKTOR MANUFAKTUR UNTUK MENINGKATKAN DAYA SAING - Aditya yoga pratama; Ribangun bamban Jakaria (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In the industrial sector, the implementation of the right financial strategy can contribute to increasing the company's business competition. There are several factors that can contribute to increasing the competitiveness of the manufacturing industry, such as capacity and capacity development, production cost management, product quality improvement, application of the latest technology, reduction of logistics costs, and government support through economic and non-economic incentives. In addition, efforts to implement strategies to advance business and increase the competitiveness of MSMEs can also play an important role in advancing the country's economy. Amid global economic uncertainty and increasingly intense competition, manufacturing companies need effective financial strategies to strengthen their competitive position. In this article, we describe some financial strategies that manufacturing companies can use to achieve sustainable growth and adapt to market changes. By maximizing the utilization of existing resources, investing in the latest technologies, and implementing efficient risk management, the company is able to gain the competitive advantage needed to strengthen the manufacturing sector and support the country's economic growth. To achieve a high level of competitiveness, strategic focus includes diversifying products within the portfolio, empowering local suppliers, and using technological innovation. In addition, cooperation with the government, foreign market development, and labor empowerment form an integral part of efforts to increase the role of the manufacturing sector in the country's economic development